2020
DOI: 10.1096/fba.2019-00090
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin‐1 mediates Drp‐1 signaling following ischemia reperfusion in the aging heart

Abstract: Ischemia reperfusion (IR) injury leads to activation of dynamin‐related protein (Drp‐1), causing mitochondrial fission and generation of reactive oxygen species (ROS), but the molecular mechanisms that activate Drp‐1 are not known. The purpose of this study was to establish the signaling pathway between Thbs‐1/CD47 and fission protein (Drp‐1) through PGC‐1 following IR in advancing age. Methods Female Fischer‐344 rats were divided into 4 groups: Young Control, Young+IR, Old Control and Old+IR. Echocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…A recent study ( in vivo and in vitro ) showed that thrombospondin mediates Drp1 signaling after ischemia/reperfusion in aged hearts. Using RAEC, an association was shown between thrombospondin and Drp1 through PGC1a 132 . In post-ischemic heart, loss of PGC1α levels facilitated mitochondrial fragmentation and promotes cardiac dysfunction 132 .…”
Section: Role Of Mqc In Coronary Microvascular Ecs Injury During MImentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study ( in vivo and in vitro ) showed that thrombospondin mediates Drp1 signaling after ischemia/reperfusion in aged hearts. Using RAEC, an association was shown between thrombospondin and Drp1 through PGC1a 132 . In post-ischemic heart, loss of PGC1α levels facilitated mitochondrial fragmentation and promotes cardiac dysfunction 132 .…”
Section: Role Of Mqc In Coronary Microvascular Ecs Injury During MImentioning
confidence: 98%
“…Using RAEC, an association was shown between thrombospondin and Drp1 through PGC1a 132 . In post-ischemic heart, loss of PGC1α levels facilitated mitochondrial fragmentation and promotes cardiac dysfunction 132 . This suggests that PGC1α-related mitochondrial biogenesis can potentially alleviate pathogenesis underlying mitochondrial dynamics-related disorders.…”
Section: Role Of Mqc In Coronary Microvascular Ecs Injury During MImentioning
confidence: 98%
“…A previous study demonstrated that ischemic damage increased the formation of oxyradicals conducted by complex III in the aging heart which overlapped with the pre-existing aging defects [ 91 ]. Increased myocyte apoptosis and the oxidative modification of mitochondrial proteins also supports the greater mitochondria-derived oxidative damage in the aged heart during I/R [ 93 , 94 ]. Moreover, the impairment of mitochondrial OXPHOS and the excessive ROS with aging during myocardial I/R exacerbates impaired metabolic flexibility [ 93 ], resulting in more severe contractile dysfunction [ 95 ] and the intolerance to I/R stress in the aged heart [ 36 , 84 , 93 ].…”
Section: Reactive Oxygen Species In Age-related Ischemic Heart Dismentioning
confidence: 99%
“…Drp-1 is a key protein involved in mitochondrial fission and ROS signaling. Inhibitors of TSP1 may potentially reduce cardiomyocyte damage and aging by reducing production of Drp-1 ( 32 ).…”
Section: Tsp1 In Cardiovascular Diseasesmentioning
confidence: 99%